Analysis of clinical effectiveness of complex therapy of generalized periodontitis in patients with gout - Gnid’, Марія Романівна; Vynogradova, Олена Миколаївна (Actual Dentistry, 2023)
Resume. Gout is a common disease, the basis of which is a violation of purine metabolism ith an increased concentration of uric acid in the blood, xcessive deposition of uric acid salts in he tissues of the musculoskeletal system and internal organs, with the subsequent development f inflammatory and, later, destructive and sclerotic changes in them. One of the relevant interdisciplinary problems is comorbidity in gout, which is closely related to cardiovascular pathology, chronic kidney disease, and metabolic syndrome, which includes diabetes, obesity, hypertension, and dyslipidemia. In connection with the steady trend towards a significant "rejuvenation" of patients with gout, considerable interdisciplinary scientific interest is caused by the search for relationships between gout and periodontal pathology. The aim of the study was to analyze the clinical effectiveness of complex pathogenetic treatment of generalized periodontitis in patients with gout. For the complex treatment of generalized periodontitis, 70 patients with gout were divided into 2 groups: the main group of patients was treated according to the developed pathogenetic scheme, the control group (35 humans) used traditional methods. The complex treatment of generalized periodontitis in patients with gout involved a combination of various therapeutic approaches and included professional oral hygiene and drug therapy. In the subjects of the main group, who used the developed pathogenetically directed scheme for the treatment of generalized periodontitis, a significant improvement in the state of the periodontal tissues was observed: the elimination of the inflammatory process and bleeding gums, a decrease in the depth of the periodontal pockets during all periods of observation. In the patients of the control group , who were treated with generally accepted methods, a noticeable improvement in the periodontal status was observed only after 1 month. In the long term of observation, there was a gradual progression of the pathological process in the periodontium, which testified to the insufficient effectiveness of the treatment of GP.